Analisis Faktor yang mempengaruhi Penggunaan E-Learning Madrasah pada Pembelajaran Tatap Muka - Dewi Setyawati; Dian Ernaningsih; Yulimira Syafriati (Jurnal Syntax Transformation, 2022)
During and after the coronavirus disease (Covid) pandemic, Madrasah schools, one of the educational institutions under the Ministry of Religion, have decided that all Madrasah schools will use the Madrasah E-Learning application for distance learning. The purpose of this study is to find out what causes schools to continue to use e-learning religious schools in face-to-face learning. Knowing the obstacles faced by teachers and students in using e-learning in face-to-face learning in religious schools. Learn about teacher and student efforts to overcome barriers to using madrasa e-learning in face-to-face learning. This study uses a qualitative method. Data collection techniques through observation, interviews, and documentation. The results show: (1) factors that influence the use of madrasa e-learning in face-to-face learning, namely, usability, not being bound by time and place, and benefits. (2.) constraints in the use of madrasa e-learning in face-to-face learning, namely internet quotas and inadequate devices. Besides internet access which is often slow, there are also some students and teachers who do not have electronic devices to carry out learning using e-learning madrasas. (3) Efforts have been made in dealing with the obstacles of using madrasa e-learning in face-to-face learning, namely: schools allocate boss funds, for the need for quota packages for teachers and students and the Ministry of Religion also provides free internet packages for teachers and students to process learning.